2016
DOI: 10.1186/s12903-016-0287-8
|View full text |Cite|
|
Sign up to set email alerts
|

Inequalities in the frequency of free sugars intake among Syrian 1-year-old infants: a cross-sectional study

Abstract: BackgroundHigh frequency of free sugars intake, during the first year of life is probably the greatest risk factor for early childhood caries. The latter is a global public health challenge. Very little is known about the social determinants of infant’s frequency of free sugars intake, particularly in low-income countries. Thus, the present study aimed to assess the association between the frequency of free sugars intake among 1-year-old Syrian infants and each of parents’ socioeconomic position (SEP), materna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(19 citation statements)
references
References 16 publications
0
17
0
2
Order By: Relevance
“…Although breastfeeding is the most common type of infant feeding in Syria some poor feeding practices were identified. A recent cross-sectional study that targeted 1 year old Syrian infants attending vaccination clinics in Damascus found that 47% of infants were breastfed, 42% were breast and bottle fed and 11% were exclusively bottle fed (11). The use of exclusive bottle feeding was more common amongst working mothers (11).…”
Section: Risk Factors For Ecc Amongst Syrian Childrenmentioning
confidence: 99%
See 3 more Smart Citations
“…Although breastfeeding is the most common type of infant feeding in Syria some poor feeding practices were identified. A recent cross-sectional study that targeted 1 year old Syrian infants attending vaccination clinics in Damascus found that 47% of infants were breastfed, 42% were breast and bottle fed and 11% were exclusively bottle fed (11). The use of exclusive bottle feeding was more common amongst working mothers (11).…”
Section: Risk Factors For Ecc Amongst Syrian Childrenmentioning
confidence: 99%
“…A recent cross-sectional study that targeted 1 year old Syrian infants attending vaccination clinics in Damascus found that 47% of infants were breastfed, 42% were breast and bottle fed and 11% were exclusively bottle fed (11). The use of exclusive bottle feeding was more common amongst working mothers (11). Nearly 50% of Syrian infants who used the bottle were put to sleep with the bottle (11, 12), increasing therefore the risk of having ECC.…”
Section: Risk Factors For Ecc Amongst Syrian Childrenmentioning
confidence: 99%
See 2 more Smart Citations
“…Unfortunately, the original version of this article [ 1 ] was missing funding information within the funding section.…”
Section: Erratummentioning
confidence: 99%